2014
DOI: 10.1155/2014/573268
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Time CT Perfusion Acquisitions Are Sufficient to Measure the Permeability Surface Area Product with a Deconvolution Method

Abstract: Objective. To reduce the radiation dose, reduced time CT perfusion (CTp) acquisitions are tested to measure permeability surface (PS) with a deconvolution method. Methods and Materials. PS was calculated with repeated measurements (n = 305) while truncating the time density curve (TDC) at different time values in 14 CTp studies using CTp 4D software (GE Healthcare, Milwaukee, WI, US). The median acquisition time of CTp studies was 59.35 sec (range 49–92 seconds). To verify the accuracy of the deconvolution alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…To the best of our knowledge, this is the first study which has compared the same series of lesions by using both multiphasic CT and CTp. CTp allows the quantitative evaluation of a tissue perfusion whilst also optimising the acquisition protocol and has shown promising results in the oncologic field, even in RCC characterisation [10,21,22]. Like the recent studies, we found significant differences in PS and MTT values between malignant lesions (clear cell RCCs, papillary RCCs, and chromophobe RCCs) and the normal renal cortex ( < 0.001 and = 0.029, resp.…”
Section: Discussionsupporting
confidence: 67%
“…To the best of our knowledge, this is the first study which has compared the same series of lesions by using both multiphasic CT and CTp. CTp allows the quantitative evaluation of a tissue perfusion whilst also optimising the acquisition protocol and has shown promising results in the oncologic field, even in RCC characterisation [10,21,22]. Like the recent studies, we found significant differences in PS and MTT values between malignant lesions (clear cell RCCs, papillary RCCs, and chromophobe RCCs) and the normal renal cortex ( < 0.001 and = 0.029, resp.…”
Section: Discussionsupporting
confidence: 67%
“…In another part of Kubo's review, it was also noted that two other studies conducted between 2000 and 2003 reported decreased nodule detectability in images obtained with less than 20 mAs, as an exposure parameter; hence, this may be an important imaging threshold to evaluate [40]. Finally, when comparing LDCT with standard dose CT, there was no statistical significance in nodule detection (LDCT vs. Standard; 518 vs. 533), with varying nodule sizes: < 3, 3-4.9, 5-6.9, 7-9.9 and ≥ 10 mm used in this and other studies [52][53][54].…”
Section: Ggo Detection Using Ldctmentioning
confidence: 61%
“…To the best of our knowledge, this is the first study which has compared the same series of lesions by using both multiphasic CT and CTp. CTp allows the quantitative evaluation of a tissue perfusion whilst also optimising the acquisition protocol and has shown promising results in the oncologic field, even in RCC characterisation [ 10 , 21 , 22 ]. Like the recent studies, we found significant differences in PS and MTT values between malignant lesions (clear cell RCCs, papillary RCCs, and chromophobe RCCs) and the normal renal cortex ( P < 0.001 and P = 0.029, resp.…”
Section: Discussionmentioning
confidence: 99%